(untitled) (The Shivapuri Journal, 2024)
This article provides a distinct examination of Nepal’s strategic orientation on national security, intricately dissecting the dynamic interplay between security imperatives, economic prosperity, and sustainability. It will discuss the economic foundations, scrutinize trade policies, investment strategies, and economic development plans, and unravel their role in fostering fiscal resilience and shaping the nation’s capacity to navigate external challenges. The environmental factor emerges as a strategic imperative, recognizing the inseparable link between a secure environment and long-term national well-being. The socio-economic dynamics explored in-depth will reveal policies contributing to citizens’ well-being and recognizing the population as a strategic asset. The integration of technological innovations is identified as a dynamic force shaping Nepal’s national security approach and positioning the nation within the global economic setting. The role of public awareness and informed citizenship is also highlighted in shaping the nation’s path. This article unfolds as a comprehensive description that unstitches the layers of complexity defining Nepal’s unique path toward a secure, prosperous, and sustainable future.